ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INVESTASI DALAM NEGERI DI INDONESIA - Safaruddin, Baso; Millia, Heppi; Suriadi, La Ode (Jurnal Ekonomi Pembangunan (JEP) UHO, 2023)
This study aims to analyze determine the effect of credit interest rates, inflation dan gross domestic product on domestic investment in Indonesia. This research uses multiple linear regression analysis method. The data used in this research is secondary data on domestic investment, credit interest rates, inflation, and gross domestic product sourced from Investment Coordinating Board, Central Statistics Agency and Bank Indonesia in 2011-2020. The results of this study indicate that (1) Credit interest rates, inflation, gross domestic product simultaneously have a significant effect on domestic investment in Indonesia, with a significance value of 0,000 < 0,05. (2) Credit interest rates partially have a negative and insignificant effect on domestic investment in Indonesia, whit a significance value of 0,470 > 0,05. (3) Inflation partially have a positive and significant effect on domestic investment in Indonesia, whit a significance value of 0,031 < 0,05. (4) Gross domestic product partially have a positive and significant effect on domestic investment in Indonesia, whit a significance value of 0,000 < 0,05.